Ocular side effects of antiphysicotic agents - Ozden, S.; Kalkan Oguzhanoglu, N.; Akyol, N.; Kukner, S.; Celiker, O.U. (My University, 1994)
Ocular complications caused by antiphysicotic agents studied on 47 patients (average age 37.8) who were under medical treatment at least one year. Average time for drug use was 4.87 years (± 4.38), mostly used medications were phenotiazine and butyrophenon, in the great majority of cases, two agents were used in combination. Frequently established ocular changes were conjunctival pigmentation (19.5%) lenticular opacities (8.7%) and retinal pigment clumpings (2.2%). Compared with healthy controls, well cooperated patients showed diminished mean sensitivity and increased defect scores in computerized perimetric examination which were all statistically significant (p<0.05).
ANTIPSIKOTIK ILACLARIN YAN ETKILERI
Keywords: Clorpromazine; Computerized perimetry; Haloperidol; Pigmentary retinopathy; Thioridazine